Comparative analysis of oral saliva microbiomes and metabolites in Han population at different altitudes - Li, Junping; Suonan, Lamu; Lin, Jiangsong; Zhaxi, Jiangcuo; Gong, Ming; Li, Jian; Langjie, Dawa; Zhu, Lulu; Shique, Qiangjiu; Chen, Cheng (Frontiers in Microbiology, 2024)
ObjectiveThis study investigated the differences in oral saliva microbiota composition and metabolic products among Han Chinese populations living at different altitudes, as well as their correlations.MethodThe analysis was conducted using the 16S rRNA gene sequencing method and untargeted metabolomics.Results16S gene sequencing results showed significant differences in bacterial diversity and composition between HH (High altitude Han) group and LH (Low altitude Han) group. LEfSe analysis showed that Selenomonas, Leptotrichia, Veillonella, Prevotella relatively abundant are higher in HH group, Haemophilus, Neisseria, Actinobacillus, Aggregatibacter are higher in LH group (p<0.05). Furthermore, as depicted in the phylogenetic tree, there are differences observed between the two groups at all taxonomic levels: 4 phyla, 6 classes, 6 orders, 9 families, 9 genera and 8 species (p<0.05). After conducting PICRUSt functional prediction analysis, we identified 11 significantly different KEGG categories (level 2) between the two groups. These categories primarily encompass energy metabolism, amino acid metabolism, and carbohydrate metabolism. Furthermore, non-targeted metabolomics analysis revealed a total of 997 distinct metabolites in the two groups. These differentiated metabolites can be classified into 13 Class I categories including amino acids and their metabolites, benzene and its derivatives, organic acids and their derivatives, heterocyclic compounds, aldehydes, ketones and esters, nucleotides and their metabolites among others. Additionally, fatty acyl compounds, alcohols and amines as well as glycerophospholipids are present along with carbohydrates and other physiologically active components such as hormones. Finally, Pearson correlation analysis of the top 20 differential metabolites with microorganisms demonstrated an interaction between them; however further experimental verification is required to elucidate the specific mechanism of action.ConclusionTherefore, this study revealed the effect of altitude on oral saliva microbes and metabolites, as well as their correlations.